Os enunciados da função social da escola nos discursos de educandos jovens e adultos - Eduardo Jorge Lopes da Silva (Universidade Estadual Paulista Júlio de Mesquita Filho, 2013)
The school is still a privileged institution for many students from education modality for youths and adults (EJA), since it provides an opportunity, among other things, the access to socially valued knowledge and qualifies these students with tools of reading, writing and basic fundamentals of mathematics. This paper investigates the discourses on the social function of school from students and young adults in a public school located in the community Mumbaba I, in the industrial district of João Pessoa / PB. The theoretical framework is based on the discourse analysis from an archaeological perspective advocated by Foucault (2000). The data were collected through semi-structured interviews. The results showed discourses that converge to an understanding that the school is the gateway to the linguistic codes, the character formation and professional training which are essential elements that provide students from lower classes a better social interaction and tools for their full achievement of citizenship.